Theory and practice of government accounting in Nigeria - Omolehinwa, Eddy O.; Naiyeju, J. K. (Lagos, Nigeria : Pumark Nigeria Limited, 2011)
The book discusses the developments in government accounting in Nigeria. It also covers the key institutions and officials involved in government accounting, cash planning and management, sources and allocation of revenue, government special accounts and public accountability among others.
.Includes bibliographical references and index
oif 24/12/13, usc 07/06/17
Loans
Keywords: .Accounting; Government accounting; Finance; Nigeria